Glycogen Rich Clear Cell Carcinoma Pada Payudara - Finot, Finot; Puspasari, Dik; Amarwati, Siti (Medica Hospitalia : Journal of Clinical Medicine, 2019)
Background: Glycogen rich clear cell carcinoma is a rare neoplasm of the breast, with the incidence of 1.4-3% of all breast cancers. The tumour has distinct morphology, different from that of common breast cancers. Glycogen rich clear cell carcinomas are members of a heterogeneous group of neoplasms, including signet-ring, secretory and lipid-rich carcinomas of the breast. In general, clear cell breast carcinoma tends to follow an aggressive clinical course. Case report: To present a case of a 47 years old woman suffering from breast mass in the upper outer quadrant of her right breast. On macroscopic examination, the biopsy tumor sized 2x1.5x0.5 cm and solid with brown and white. Discussion: Microscopic examination showed breast tissue composed of tumor cells arranged in nets, trabeculae and singly dispersed. Tumor cells are moderately pleomorphic, have sharply defined border and polygonal contours. Cytoplasm is clear in more than 90% of cells and finely granular in few cells. Nuclei are hyperchromatic with clumped chromatin and prominent nucleoli. Occasional mitosis is also observed. Special stain (PAS Staining): Intracytoplasmic PAS positivity in tumor cells are variable. Immunohistochemistry ER (+) positive >20-50%, PR (+) positive <20%, HER2 (-) negative. The patient was diagnosed with glycogen rich clear cell carcinoma. Conclusion: Glycogen rich clear cell carcinoma of the breast is rare. Its clinical feature is rather aggressive and varies depending on special characteristics such as low grade. Keywords: Glycogen rich clear cell carcinoma, breast carcinoma, PAS staining Latar belakang: Glycogen rich clear cell carcinoma adalah kanker payudara yang jarang, dengan insidensi 1.4-3% dari semua kanker payudara. Tumor memiliki morfologi yang berbeda dari kanker payudara pada umunya. Glycogen rich clear cell carcinoma merupakan neoplasma heterogen yang termasuk karsinoma payudara signet-ring, sekretori dan kaya lipid. Secara umum, carcinoma ini cenderung mengikuti perjalanan klinis yang agresif. Tujuan: Laporan Kasus: Dilakukan pemeriksaan makroskopis jaringan tumor dari seorang perempuan berusia 47 tahun dengan massa payudara kanan di kuadran luar atas. Tumor biopsi berukuran 2x1.5x0.5 cm, komposisi padat, berwarna coklat dan putih. Dilakukan pemeriksaan histopatologi, imunohistokimia dan histokimia pewarnaan khusus PAS (Periodic Acid Schiff). Pembahasan: Pemeriksaan mikroskopis menunjukkan jaringan payudara dengan sel-sel tumor yang tersusun dalam jaring, trabekula dan tersebar tunggal. Sel-sel tumor cukup pleomorfik, hiperkromatik, kromatin kasar dan nucleoli prominent, mitosis dapat ditemukan, sitoplasma jernih lebih dari 90% sel dan granular halus dalam beberapa sel, memiliki garis batas dan beberapa bentuk poligon yang jelas. Hasil histokimia PAS (+) positif, Immunohistokimia ER (+) positif > 20-50% pada sel-sel tumor, PR (+) positif < 20%, HER2 (-) negatif. Dari hasil pemeriksaan tersebut, pasien didiagnosis Glycogen rich clear cell carcinoma. Kesimpulan: Glycogen rich clear cell carcinoma pada payudara adalah tumor yang jarang, perilaku klinisnya dilaporkan agak agresif sejauh ini, sangat bervariasi tergantung pada karakteristik khusus seperti tingkat rendah. Kata kunci: Glycogen rich clear cell carcinoma, karsinoma payudara, pewarnaan PAS.